Behaviour change interventions to promote prescribing of generic drugs: a rapid evidence synthesis and systematic review. Issue 5 (14th May 2014) - Moe-Byrne, Thirimon; Chambers, Duncan; Harden, Melissa; McDaid, Catriona
Abstract : Objective: To summarise evidence on the effectiveness of behaviour change interventions to encourage prescribing of generic forms of prescription drugs where clinically appropriate in the UK National Health Service (NHS) and similar settings. Design: Systematic review. Search strategy: We conducted a rapid evidence synthesis in two stages: First, we searched databases, such as the Cochrane Database of Systematic Reviews (CDSR) and Database of Abstracts of Reviews of Effects (DARE), for systematic reviews of interventions that reported outcomes related to utilisation of generic drugs. In the second stage, we searched several databases including MEDLINE and EMBASE to identify primary studies of any interventions not covered by systematic reviews. Data extraction and quality assessment: Data were extracted into a standardised data extraction form. Standardised quality assessment tools were used to assess study quality. Two reviewers were involved in data extraction and quality assessment. Results: 10 reviews were included for the initial evidence synthesis, but most were of limited usefulness to our focused review question. One review evaluated the effect of prescribing policies using financial incentives and showed an increase in generic prescribing. Thirteen primary studies of other interventions were included for the rapid review. Two studies showed an increase in percentage of overall generic prescribing with an educational intervention; two studies showed an improvement in generic prescribing rates when physicians collaborated with pharmacists, though in one study this was not statistically significant; two US studies showed improvements in generic prescribing with electronic prescribing. Five out of seven studies showed positive results with multifaceted interventions. Conclusions: The existing evidence remains insufficient to determine which behaviour change intervention or combination of interventions is most effective due to methodological weaknesses and conflicting results. Based on the evidence, financial incentives with educational intervention and audit/feedback look promising but decision-makers should take into account the practicality and costs of the interventions before implementation.